Highly Pressure‐Sensitive, Temperature Independent Luminescence Ratiometric Manometer Based on MgO:Cr3+ Nanoparticles. Issue 4 (11th January 2023) - Szymczak, Maja; Runowski, Marcin; Lavín, Victor; Marciniak, Lukasz
Abstract: Reliable remote pressure readout is possible only if high sensitivity of the measurement and independence from other physical factors are ensured. Among the parameters most strongly affecting measurements, temperature plays the most important role. In luminescence manometry, ratiometric measurement facilitates rapid pressure measurement ensuring high sensitivity of measurement while maintaining accuracy. Therefore, this paper compares the manometric performance of two ratiometric approaches in the material based on the luminescence of Cr 3+ ions: using the intensity ratio of 2 E→ 4 A2 to 4 T2 → 4 A2 and a new approach based on the luminescence intensity ratio of 4 T2 → 4 A2 band recorded in two spectral ranges. Using the first approach, a manometer with an unprecedented sensitivity of S R = 40% GPa −1 is developed. However, the second approach provides completely temperature‐invariant pressure measurement with a sensitivity of S R = 9.8% GPa −1 . The presented results indicate that the MgO:Cr 3+ nanoparticles are a highly reliable and sensitive candidate for a new luminescent manometer. Abstract : Manometric performance of two ratiometric approaches in the material based on the luminescence of Cr 3+ ions is compared: using the intensity ratio of 2 E→ 4 A2 to 4 T2 → 4 A2 and a new approach based on the luminescence intensity ratio of 4 T2 → 4 A2 band recorded in two spectral ranges.